2019
DOI: 10.1108/jocm-10-2017-0387
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating creative workplaces through mindfulness

Abstract: Purpose The purpose of this paper is to examine how mindfulness training impacts creativity with individuals in a workgroup and propose a methodology for future research. Design/methodology/approach The methodology developed drew on existing laboratory-based research and applied those designs in a real-world application. The sample participants were from a mid-sized real estate firm that included ten realtors and support staff, six in the treatment group and four in the comparison group. The study took place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 46 publications
2
28
0
2
Order By: Relevance
“…For instance, Dane and Brummel (2014) investigated the impact of being mindful in a dynamic work environment and found that being present in the moment and being able to pay full attention to various stimuli and events was positively related to performance at work. Moreover, mindfulness is also positively associated with creativity, affective commitment, job satisfaction and engagement (Andrews et al , 2014; Byrne and Thatchenkery, 2019; Malinowski and Lim, 2015; Zivnuska et al , 2016). Zivnuska et al (2016) argue that mindfulness enables employees to recognise and respond to various stimuli and situations more appropriately and it provides access to other psychological resources, which may work in favour of well-being and positive job-related attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dane and Brummel (2014) investigated the impact of being mindful in a dynamic work environment and found that being present in the moment and being able to pay full attention to various stimuli and events was positively related to performance at work. Moreover, mindfulness is also positively associated with creativity, affective commitment, job satisfaction and engagement (Andrews et al , 2014; Byrne and Thatchenkery, 2019; Malinowski and Lim, 2015; Zivnuska et al , 2016). Zivnuska et al (2016) argue that mindfulness enables employees to recognise and respond to various stimuli and situations more appropriately and it provides access to other psychological resources, which may work in favour of well-being and positive job-related attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity and dynamics of the current competitive environment, innovation has become an essential ingredient to gain a competitive advantage (Bomberg, 2014;Byrne and Thatchenkery, 2019;Mayfield and Mayfield, 2017a). For decades, researchers have had an enduring interest in organizations' creative environments, for they contribute to innovation and thus organizations' ability to outperform their competitors (Conger, 1995;Dong et al, 2017;Litchfield et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the importance of constructing sensory systems, the search for creative destruction and the cultivation of connections to increase an organization's resilience and its capacity to deal with the unexpected have been underlined (Schwartz, 2003). Furthermore, cultivating creative workplaces through mindfulness (Byrne and Thatchenkery, 2019) provides qualities relevant for change.…”
Section: Practical Political and Theoretical Implicationsmentioning
confidence: 99%